Subsidizing children with breakfast can help in reducing malnutrition harms: the experience of the Monte Albán community intervention program of AVSI in Mexico - Martinez Piñeiro, A.L.; Ballali, S.; Baldi, I.; Vecchio, M.G.; del Socorro del Rio Angulo, M.; Stanchi, R.; Gregori, D. (Progress in Nutrition, 2013)
In the latest years the fight against malnutrition has led to the development of several community- based programs, meant at sustaining normal growth and development of the weakest strata of the population. AVSI, together with the Mexican partner CRECEMOS, has founded a project aimed at providing daily breakfast to the children of the community of Monte Albán, Oaxaca, Mexico. Considering the short term and long term effects of nutrient’s insufficiency, several programs have been targeted for growth promotion showing greater results when children could profit not only from improved nutrition but also from improved learning opportunities in the earliest years of life. The present retrospective study has therefore two main purposes, to compare growth status of Monte Albán children with the national one and second to evaluate the impact of  the project on the growth status of children afferent to the association on a regular basis.Sostenere i bambini con un progetto incentrato sulla colazione può aiutare a ridurre le patologie legate alla malnutrizione: l’esperienza nella comunità di Monte Albán del programma di intervento della Fondazione AVSI in MessicoNegli ultimi anni la lotta contro la malnutrizione ha portato allo sviluppo di vari programmi su base comunitaria, con lo scopo di sostenere la normale crescita e lo sviluppo delle fasce più deboli della popolazione. AVSI, insieme al partner messicano CRECEMOS, ha fondato un progetto volto a fornire giornalmente la prima colazione ai bambini della comunità di Monte Albán, Oaxaca, Messico. Considerando gli effetti della malnutrizione, sia a breve che a lungo termine, i diversi programmi si sono focalizzati sulla promozione della crescita, dando maggiori risultati quando i bambini erano messi in condizione di beneficiare non solo di una migliore alimentazione, ma anche della possibilità di avere un sostegno all’apprendimento nei primi anni di vita. Il presente studio retrospettivo ha quindi due scopi principali, di confrontare lo stato di crescita dei bambini Monte Albán rispetto agli standard nazionali, e di valutare l’impatto del progetto AVSI sullo stato di crescita dei bambini regolarmente afferenti alla struttura.